Trade potential, intra-industry trade and factor content of revealed comparative advantage in the Baltic Sea region - Mika Widgrén (The Research Institute of the Finnish Economy (ETLA), 2006)
This paper investigates trade potential, intra-industry trade and comparative advantage in the Baltic Sea Region. The evaluation of region's comparative advantage and intra-industry trade are based on the Balassa index of revealed comparative advantage and the Grubel-Lloyd index respectively. The analysis is carried out at HS 4-digit level. Trade potential is assessed using applying earlier versions of the gravity model of international trade. The actual trade flows analysis suggest that the BSR has reached its potential importance in intra-EU25+ (EU25, Norway and Russia) trade. In this respect the countries within BSR differ, however, considerably. BSR's share falls considerably below its potential share in Russia's, Latvia's and Norway's European exports. The overall conclusion in trade potential analysis is that the centre of gravity within BSR is likely to move gradually from Stockholm-Hamburg –axis somewhat to the east. The major part of the analysis concentrates on the factor intensities of the Baltic Sea Region's comparative advantage and its overlap with a sample of other countries. The analysis demonstrates surprisingly big changes in some Baltic Sea Region's countries specialisation patterns. The paper shows that in nearly all countries in the Baltic Sea Region the factor contents of revealed comparative advantage has shifted towards less physical capital intensive and more human capital intensive direction. Especially, Finland, Estonia and Poland are best examples in this respect. In 1996, the picture of the factor contents of the region's comparative advantage was clearly polarised but there has been some convergence after that. In terms of intra-industry trace the region can be divided to the northern and southern triangles. The former consists of Finland, Sweden and Estonia and the latter of Germany, Denmark and Poland. These two are linked via Sweden.
Keywords: F10; F15; 330; comparative advantage; factor intensity; Baltic Sea region; Komparativer Kostenvorteil; Intraindustrieller Handel; Außenhandelsstruktur; Faktorintensität; Ostsee